TINJAUAN YURIDIS PENENGGELAMAN KAPAL ASING MENURUT UNDANG-UNDANG NOMOR 45 TAHUN 2009 TENTANG PERIKANAN - Elisabeth Septin Puspoayu; Bunga Nurani; Esti Wulan Trityas; Maulida Indah Sari; Mayang Chandra Gita Siti; Allafa Qori’atul Muzayyanah (Universitas Muhammadiyah Malang, 2021)
Amendment to the United Nations Convention on the Law of the Sea of 1982 with Law No. 17 the Year 1985 makes Indonesia have the right to utilize, conservation, and manage fish resources in Indonesia's exclusive economic zone and the high seas. Such rights are exercised under applicable international terms or standards. Therefore, legislation was made related to the sinking of illegal fishing vessels in Indonesian territorial waters through Law No. 45 of 2009 on Fisheries. Indonesia's high wealth of marine resources does not run following all layers' expectations after illegal fishing. However, the juridical consequences of applying the law have several impacts, namely the impact of sinking foreign vessels on relations with foreign countries and negative-positive effects in the marine environment due to the sinking of foreign vessels illegal fishing actors.